Short-run and long-run effect of oil consumption on economic growth: ECM model - Sofyan Syahnur; Endra Endra; Said Muhammad (Universitas Islam Indonesia, 2014)
The aim of this study is to investigate the effect of oil consumption on economic growth of Aceh in the long-run and short-run by using Error Correction Model (ECM) model during the period before the world commodity prices fall of 1985–2008. Four types of oil consumption will be focused on Avtur, Gasoline, Kerosene and Diesel. The data is collected from Central Bureau of Statistics of Aceh (BPS Aceh). The result of this study shows a merely positive effect of oil consumption type diesel to economic growth in Aceh both in the short run and the long run.